Influence of geometrical and material parameters on flow rate in simplified ADS dense granular-flow target: a preliminary study. Issue 11 (1st November 2016) - Wan, Jiang-Feng; Zhang, Sheng; Tian, Yuan; Lin, Ping; Yang, Guanghui; Yang, Lei
ABSTRACT: The spallation target is one of the key components of an accelerator-driven subcritical system (ADS). Following previous designs such as plate targets, rod targets, rotating targets, and liquid metal targets, the gravity-driven dense granular-flow target (DGT), which combines the advantages of solid and liquid metal targets, becomes a new attractive choice. The geometry of DGT consists of a cylindrical hopper and an internal coaxial cylindrical beam pipe. In this paper, using discrete element method simulations on graphics processing units, we research into the relations of the flow rate with the geometrical as well as the material parameters. For geometrical parameters, it is found that the existence of an internal pipe does not influence the flow rate when the distance from the bottom of the pipe to orifice is large enough. The results also reveal how the material parameters influence the flow rate. The whole research is helpful for the design of DGT.